Fundamental elements of constant volt/hertz induction motor drives based on dSPACE DS1104 controller - Siti Nursyuhada Mahsahirun; Nik Rumzi Nik Idris; Zulkifli Md. Yusof; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
An induction motor (IM) has been the workhorse of the industry for decades. It is due to its robustness, simple construction, requiring less maintenance and cheap. One of the most widely adopted IM drive control schemes for industrial applications is the open-loop constant V/Hz. In this paper, the important elements of an open-loop constant V/Hz drives are presented. These include the fundamental concept of a constant V/Hz scheme, the voltage source inverter (VSI) and its modulation schemes. Techniques that are commonly used to solve problems of low-speed operation and rotor speed regulation are briefly described. Simulations using MATLAB/Simulink package are used to help in illustrating these fundamental concepts. Finally, simple laboratory-scale experiments are conducted to implement the constant V/Hz control scheme on a ¼ hp induction motor. The constant V/Hz control is implemented using the DS1104 controller board with the C codes automatically generated from the Simulink model. A closer look at the current waveform when fref=25 Hz and 12 Hz and its respective Fourier analysis are presented. The results show that the high-frequency harmonic contents around the switching frequency can be observed for both cases, and the voltage waveform presents more spike noises in constrast to  current waveform.